ITIL® 4 : direct, plan and improve : reference and study guide (TSO (The Stationery Office), 2022)
The ITIL 4 Direct, Plan and Improve (DPI) reference and revision guide is one of five ITIL 4 Managing Professional titles published by TSO, following on from the ITIL 4 Foundation revision guide. It provides a grounding in a set of principles, methods, and techniques to create a learning and improving environment. It covers the influence and impact of Agile and Lean ways of working and provides practical and strategic methods to plan and deliver continual improvement. Key topics include risk, decision-making, governance, continual improvement, assessing for improvement, developing a business case, organizational change management and communication, measuring and reporting, and value streams and practices. This pocket guide is an aid for revision and preparation for taking the ITIL 4 Managing Professional: DPI certification, and post-certification it is a quick useful reference. It summarizes key topics for exam preparation, includes key figures from the core guidance, provides an examination overview, tips for taking the exam and a summary table linking learning outcomes to references in the text and to core guidance.